ANALISIS KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) DENGAN PENDEKATAN CHOICE MODELLING (STUDY KASUS COBAN RONDO DAN COBAN TALUN - safa'atin, Ermi Safaatin; Shofwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to answer several questions related to the choices made by visitors when choosing to visit between Coban Rondo and Coban Talun and their maximum WTP evaluation for conservation purposes.This study seeks to assess how the main environmental attributes of interest to researchers will determine tourists WTP for conservation purposes.The research approach used in this study is a quantitative approach with a descriptive approach. Determination of the number of samples used in this study is a linear time function. The results of research on the characteristics of respondents, respondents' perceptions, and analysis of factors influencing tourist visits to the Wendit Water Tourism Park using the Individual Travel Cost Method (ITCM) are mostly female with an age range between 21-40 years and the level of education is mostly from undergraduate strata 1 graduates and their equivalents. The results of the Willingnes To Pay calculation of visitors to the progress of the quality of the environment and the Coban Rondo and Coban Talun pariwsata places are Rp. 2,400.00 per person. With the average number of visitors who come to Coban is about 200 in 1 month, the economic value of the two coban will be around Rp.480,000.00 in a month.